Why Trading with Dictators May Nevertheless Help the People: On the Interplay between Trade, Political Regimes and Economic Institutions - Usman Khalid (Lund University, School of Economics and Management, Department of Economics, 2015)
Recent empirical studies confirm a positive relationship between trade liberalization or trade openness and the quality of domestic economic institutions. An isolated analysis of trade openness per se, however, may grossly simplify the mechanisms at work, as the linkage between open trade and quality of economic institutions is likely to vary for different political regimes. This study examines the causal relationship between trade openness and quality of economic institutions under different political institutions. We find that in the presence of extractive political institutions, the effect of trade openness on economic institutions is reduced significantly.
Keywords: F13; F14; P14; P16; 330; trade openness; political institutions; economic institutions; institutional change